2004
DOI: 10.2519/jospt.2004.34.9.549
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal Musculature and Skin Temperature Changes: Comparing the ThermaCare HeatWrap, the Johnson & Johnson Back Plaster, and the ABC Warme-Pflaster

Abstract: Study Design: Prospective, randomized, crossover design. Objectives: To compare the effectiveness of the Johnson & Johnson Back Plaster, the ABC Warme-Pflaster, and the ThermaCare HeatWrap on skin and paraspinal muscle temperature. Also, to compare the subjects' heat perception for the 3 products. Background: Heat therapy is a common treatment for low back pain and disability. There are a number of products on the market that are suggested to relieve low back pain by providing warmth to the back; however, thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…However, most previous studies on the efficacy of heating modalities have investigated the calf, 16 knee, 26 or lowback. 45 Less is known about the intramuscular temperature changes in larger muscles such as the vastus lateralis.Several recent thermal studies have reported increases in passive joint range of motion 36,38 ; however no studies have examined the electrical and mechanAbbreviations: ANOVA, analysis of variance; EMG, electromyography; ICC, intraclass correlation coefficient; IMF, instantaneous mean frequency; MMG, mechanomyography; MVC, maximal voluntary contraction; 2 , eta squared statistic (effect size); SEM, standard error of measurement; SD, standard deviation …”
mentioning
confidence: 99%
“…However, most previous studies on the efficacy of heating modalities have investigated the calf, 16 knee, 26 or lowback. 45 Less is known about the intramuscular temperature changes in larger muscles such as the vastus lateralis.Several recent thermal studies have reported increases in passive joint range of motion 36,38 ; however no studies have examined the electrical and mechanAbbreviations: ANOVA, analysis of variance; EMG, electromyography; ICC, intraclass correlation coefficient; IMF, instantaneous mean frequency; MMG, mechanomyography; MVC, maximal voluntary contraction; 2 , eta squared statistic (effect size); SEM, standard error of measurement; SD, standard deviation …”
mentioning
confidence: 99%
“…20 In addition to increasing the temperature on the surface of the skin, the most extensively studied of these devices also produces a rapid increase in intramuscular temperature of approximately 1°C over baseline at a depth of 2 cm for 30 minutes postapplication. [20][21][22] This is in contrast to capsaicin or capsicum-containing back plasters or menthol-containing patches, which do not produce an increase in intramuscular temperatures. 20-22 Numerous clinical studies with this heatwrap have demonstrated the effectiveness of continuous low-level heat therapy in relieving pain, muscle stiffness, and disability, and in improving lateral trunk flexibility in people with LBP.…”
Section: Discussionmentioning
confidence: 96%
“…However, the temperature increases at this level are unlikely to cause the desired effects of heat therapy, namely higher tissue temperatures, which produces vasodilation, increasing the supply of oxygen and nutrients and the elimination of carbon dioxide and metabolic waste. By contrast, heat wrap therapy and the continuous application of heat for 8-12 h has been shown to be therapeutic in a number of studies [40,41]. The temperature increases with heat wraps has been reported to be 2°C at depths of 2 cm [40,42], which are clearly not achieved with low-dose PSWD devices.…”
Section: Shortwave Electromagnetic Therapiesmentioning
confidence: 94%